Attended Versus Unattended Blood Pressure Measurement in a Real Life Setting. Issue 2 (February 2018) - Bauer, Frederic; Seibert, Felix S.; Rohn, Benjamin; Bauer, Klaus A.R.; Rolshoven, Eckart; Babel, Nina; Westhoff, Timm H.
Abstract : The debate on the generalizability of the SPRINT (Systolic Blood Pressure Intervention Trial) findings raised considerable interest in the technique of unattended office blood pressure (BP) measurement. It remains elusive, however, whether unattended BP measurement yields lower values than conventional measurements in a real world setting with subjects consulting their personal general practitioner in a familiar office. We performed a cross-sectional study in 158 patients in 4 general practitioners' offices and compared conventional auscultatory office BP to unattended automated office BP in 107 subjects (group 1) and unattended to attended automated office BP in another 51 subjects (group 2). Unattended BP was calculated as the mean of 3 automated measurements performed in a separate room after 5 minutes of rest. Additionally, patients documented home BP for 7 days after the consultation. Mean auscultatory office, unattended office and home BP were 144.6/81.0, 144.1/79.9, and 135.5/78.3 mm Hg in group 1; unattended and attended automated office BP were 134.2/80.6 and 135.7/80.6 mm Hg in group 2. Systolic attended and unattended office BP values were significantly higher than home BP ( P <0.001, P <0.01, respectively). Attended and unattended office BP, however, did neither show a significant difference in group 1 nor in group 2 ( P >0.05 each). Bland–Altman analysis revealed a bias of 0.5 mm Hg systolic and 1.1 mm Hg diastolic in group 1 and −1.5 mm Hg systolic and 0 mm Hg diastolic in group 2. In conclusion, the present findings show that unattended and attended office BP measurements achieve comparable results, if measurements take place at a familiar general practitioner's office.